The Nickel Industry in Indonesia: How Far Are the Environmental Impacts and the Legal Liability? - Hafiza Hafiza; Yeni Widowaty; Hikmah Zougira (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
One of the elements of human rights is the right to a safe and healthy environment—industrialization's role as an economic booster. However, the Konawe Nickel Industrial Area's industry impacts the environment. This research examines the legal liability for (VDNI) Virtue Dragon Nickel Industry Inc.'s environmental impacts in Morosi District, Konawe Regency. The findings revealed that the nickel smelter industry Konawe's VDNI Inc. activity resulted in a change in ambient air quality that exceeded the required air quality standard, noise disturbance that exceeded the quality of noise needed standard, as well as Toxic and Hazardous Waste (B3) waste and non-Toxic and Hazardous Waste (non-B3) taste that was still stored in one place and did not report their business activities to the Provincial and Regency Environmental and Forestry Services and the Industry and Energy Office regarding the use of coal-fired power plants in the electricity sector. As a result, VDNI Inc. must be held entirely accountable (strict liability) in administrative, civil, and criminal law.